Blastogenesis as an in vitro correlate of delayed hypersensitivity in guinea pigs infected with Listeria monocytogenes. - Fulton, A M (1975)
Randomly bred guinea pigs of both sexes were injected intracardially with one-half a 50% lethal dose of Listeria monocytogenes. When these animals were skin tested with 30 mug of a water-soluble extract of sonically disrupted Listeria, animals had uniformly detectable levels of delayed-type hypersensitivity (DTH) 6 days after infection. Histological examination of skin test reaction sites, after fixation in Helly fixative and Giemsa staining, revealed a classical tuberculin-type infiltrate consisting primarily of mononuclear cells with few polymorphonuclear cells. Many of the small vessels showed perivascular cuffing. When purified peritoneal exudate lymphocytes from these animals were cultured in vitro in the presence of various concentrations of Listeria antigen, it was fount that the optimal antigenic dose for specific antigen-induced incorporation of [3H]thymidine varied for individual animals. In contrast to the early onset of uniformly detectable levels of in vivo DTH, in vitro lymphocyte blastogenesis was not uniformly demonstrable until 14 days postinfection and remained highly significant on days 21, 28, and 84 postinfection. At 7 days postinfection, lymphocytes from 7 of 17 animals were capable of undergoing sifnificant blastogenesis. The Listeria antigen preparation was not mitogenic for peritoneal exudate lymphocytes from normal animals. It was found that no direct correlation exists between the in vivo levels of DTH and in vitro blastogenesis. Cell donors showing significant in vitro blastogenesis nevertheless were also skin test positive for most animals tested. Humoral antibody was found to play no significant role in the immune response of guinea pigs to a primary infection with Listeria monocytogenes.